Analisis Pemungutan Dan Pemotongan Atas Pajak Penghasilan Final Dan Tidak Final Bendahara Pengeluaran Kementerian - Dinar Riftiasari (Universitas Bina Sarana Informatika, 2018)
Tax is a contribution collected by the state from the central government and regional governments based on the Law, the cutting and collection of income tax for expenses derived from the State Budget by the treasurer of the Central Government and the Regions. The purpose of this study was to determine the procedure for the cutting and collection of income tax. Income tax (PPh) of Article 22 for the procurement of goods at the Ministry, income tax (PPh) of Article 23 for rent and other income in connection with the use of property, and income Tax (PPh) of Article 4 paragraph (2) for construction services. The analysis method used is descriptive method. The conclusion of the research on the purchase of goods with funds from state spending or shopping areas subject to Income Tax Article 22 amounting to 1.5% of the purchase price already have a taxpayer identification number (NPWP), Cutting of income tax article 23 for rent and other income in connection with the use of property amounting to 2% from total gross, construction service can be charged income tax based on article 4 paragraph 2 which is final. The cutting and collection of income tax is in accordance with the provisions of taxation Income Tax Law number 36 Year 2008. Keywords: income tax cuts and collection, Income Tax Article 22, Income Tax Article 23, Income Tax Article 4 paragraph 2